Prognostic Significance of Sodium Iodide Symporter and Deiodinase Enzymes mRNA Expression in Gastric Cancer - Mishra, Alok (Int J Appl Basic Med Res, 2020)
CONTEXT: Thyroid hormones (THs) are critically important for development, homeostasis, and metabolic regulation in mammals. Iodine, one of the constituents of TH, is actively supplied by sodium iodide symporter (NIS) into the thyroid gland. TH is subsequently transported to distant organs where its activation and deactivation is catalyzed by isoforms of deiodinases (DIOs). NIS protein has been known to overexpress in cancer cases of the breast and gastrointestinal organs. Recent studies show a possible role of DIOs in various cancers. AIMS: In the present investigation, the prognostic significance of NIS and DIO-1, 2 and 3 was studied in gastric cancer using a data mining bioinformatic approach. METHODS: “The Kaplan–Meier plotter” database was used for direct in silico validation in clinically relevant 876 gastric cancer patients with >15 years of follow-up information. After obtaining KM survival plots, hazard ratio and log-rank P value were calculated. RESULTS: Increased expression of NIS and DIO 1-3 is significantly associated with worsen overall survival of gastric cancer patients followed for 20 years. Prognostic roles of NIS and individual DIOs were assessed in different types of gastric cancer classified based on morphologies, human epidermal growth factor receptor-2 receptor status, treatment choices, and different clinicopathological features. CONCLUSIONS: Based on these analyses, the present study found the indication of prognostic values of these genes. This information will contribute to better understanding of managing complex and heterogeneous gastric cancer. Further, these findings may be beneficial as a companion diagnostic tool predicting more accurate gastric cancer prognosis.